Three new species of Oppiidae (Acari, Oribatida) from Mexico - Ermilov, Sergey G.; Kontschán, Jenő (Zootaxa, 2023)
Three new species of Oppiidae (Oribatida)—Graptoppia (Apograptoppia) rooensis sp. nov., Neoamerioppia (Neoamerioppia) mexicoensis sp. nov., and Ramusella (Insculptoppia) quintanaensis sp. nov.—are described based on adults collected from leaf litter in a large karst pit in the secondary semi-evergreen tropical forest in Mexico. The subgenus Graptoppia (Apograptoppia) is recorded for the first time in the Neotropical region.